Analysis of the Influence of Green Supply Chain Management on Economic Performance - Agus Abdul Aziz; Titik Kusmantini; Nilmawati (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study aims to analyze the influence of green supply chain management practices on economic performance, both directly and mediated by environmental and social performance, in furniture MSMEs in Yogyakarta. This research employs a quantitative descriptive approach, with the population being all furniture SMEs in Yogyakarta. The sampling technique used in this study is purposive sampling. The data used is primary data obtained through questionnaires and interviews. The analysis used in this study is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 4.0. The results of this study indicate that green supply chain management practices have a positive impact on environmental and social performance, but green supply chain management practices do not have a positive impact on economic performance, either directly or indirectly mediated by environmental and social performance. Meanwhile, environmental performance has a positive impact on economic performance, while social performance does not have a positive impact on the company's economic performance. Furniture SMEs in Yogyakarta should further enhance the implementation of green supply chain management practices and elaborate on them with the development of existing information technology, adapting them to the conditions of each company to be effective and efficient, thus positively impacting the company's performance.